Dispersão da Refractariedade Auricular como Substrato Electrofisiológico da Vulnerabilidade Auricular em Doentes com Fibrilhação Auricular Paroxística - Oliveira, MM (2007)
Atrial electrical remodeling plays a part in recurrence of atrial fibrillation (AF). It has been related to an increase in heterogeneity of atrial refractoriness that facilitates the occurrence of multiple reentry wavelets and vulnerability to AF. AIM: To examine the relationship between dispersion of atrial refractoriness (Disp_A) and vulnerability to AF induction (A_Vuln) in patients with clinical paroxysmal AF (PAF). METHODS: Thirty-six patients (22 male; age 55+/-13 years) with > or =1 year of history of PAF (no underlying structural heart disease--n=20, systemic hypertension--n=14, mitral valve prolapse--n=1, surgically corrected pulmonary stenosis--n=1), underwent electrophysiological study (EPS) while off medication. The atrial effective refractory period (AERP) was assessed at five different sites--high (HRA) and low (LRA) lateral right atrium, high interatrial septum (IAS), proximal (pCS) and distal (dCS) coronary sinus--during a cycle length of 600 ms. AERP was taken as the longest S1-S2 interval that failed to initiate a propagation response. Disp_A was calculated as the difference between the longest and shortest AERP. A_Vuln was defined as the ability to induce AF with 1-2 extrastimuli or with incremental atrial pacing (600-300 ms) from the HRA or dCS. The EPS included analysis of focal electrical activity based on the presence of supraventricular ectopic beats (spontaneous or with provocative maneuvers). The patients were divided into group A--AF inducible (n=25) and group B--AF not inducible (n=11). Disp_A was analyzed to determine any association with A_Vuln. Disp_A and A_Vuln were also examined in those patients with documented repetitive focal activity. Logistic regression was used to determine any association of the following variables with A_Vuln: age, systemic hypertension, left ventricular hypertrophy, left atrial size, left ventricular function, duration of PAF, documented atrial flutter/tachycardia and Disp_A. RESULTS: There were no significant differences between the groups with regard to clinical characteristics and echocardiographic data. AF was inducible in 71% of the patients and noninducible in 29%. Group A had greater Disp_A compared to group B (105+/-78 ms vs. 49+/-20 ms; p=0.01). Disp_A was >40 ms in 50% of the patients without A_Vuln and in 91% of those with A_Vuln (p=0.05). Focal activity was demonstrated in 14 cases (39%), 57% of them with A_Vuln. Disp_A was 56+/-23 ms in this group and 92+/-78 ms in the others (p=0.07). Using logistic regression, the only predictor of A_Vuln was Disp_A (p=0.05). CONCLUSION: In patients with paroxysmal AF, Disp_A is a major determinant of A_Vuln. Nevertheless, the degree of nonuniformity of AERP appears to be less important as an electrophysiological substrate for AF due to focal activation.